Pemberdayaan Masyarakat: Strategi Memerangi Islamofobia melalui Diplomasi dan Komunikasi yang Efektif: Empowering Communities: Strategies to Combat Islamophobia through Effective Diplomacy and Communication - Aswar, Hasbi; Felani, Herman (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Islamophobia is still a major problem faced by people in various parts of the world, including in Muslim-majority countries. Muslims themselves have difficulty in dealing with Islamophobia and many do not yet understand coping strategies. To strengthen the ability of the community to promote a positive image of Islam and Muslims and to educate ordinary people about Islam, certain steps need to be taken. This community service aims to provide education on strategies to overcome Islamophobia through effective diplomacy and communication strategies. This service is carried out through online seminars (Webinars) via Zoom Meetings to reach the wider community and can be recorded properly for community reference in the future. The activity which was held for two days in two weeks responded positively by participants who thought that the same agenda needed to be continuously held in the future to educate people on the issue of Islamophobia and how to deal with it.